The politics of the book : a study on the materiality of ideas - Carreira da Silva, Filipe; Brito Vieira, Mónica (Penn State series in the history of the book, 2019)
"Explores several classic works of social and political thought, examining how the history of their publication materially affected their meaning and reception over time. Case studies include works by Durkheim, Mead, Marx, Du Bois, and Weber"--Provided by publisher.
Keywords: Sociology literature : History and criticism : Case studies; Political science literature : History and criticism : Case studies; Books : Political aspects; Politics in literature; Sociology in literature; Sociologi i litteraturen; Politik i litteraturen; Böcker : politiska aspekter; sosiologia; valtio-oppi; politiikka; kirjallisuudentutkimus; kirjallisuudenhistoria; kirjat